MiR-125b Contributes to Ovarian Granulosa Cell Apoptosis Through Targeting BMPR1B, a Major Gene for Sheep Prolificacy. (February 2019) - Yao, Yilong; Reheman, Anwaier; Xu, Yefei; Li, Qifa
Bone morphogenetic protein receptor 1B (BMPR1B) is a major gene for ovine ovulation rate and litter size, which plays a crucial role in follicle development. However, its role and regulation in the ovine granulosa cells (GCs) are unclear. Here, we showed that silencing of BMPR1B enhanced cell apoptosis, whereas overexpression of BMPR1B inhibited cell apoptosis in the ovine GCs. Luciferase reporter assays revealed that BMPR1B is a target of miR-125b, and miR-125b reduced BMPR1B messenger RNA and protein levels in the ovine GCs by directly binding to the 3′ untranslated region of the ovine BMPR1B gene. Furthermore, miR-125b enhanced cell apoptosis by attenuating BMPR1B in the ovine GCs. Our data demonstrated that BMPR1B is an important factor in the ovine GC function in vitro and targeted by a specific regulator miR-125b.